Biliary and vascular anomalies in living liver donors: the role and accuracy of pre‐operative radiological mapping. Issue 9 (1st February 2013) - Segedi, Maja; Buczkowski, Andrzej K.; Scudamore, Charles H.; Yoshida, Eric M.; Harris, Alison C.; DeGirolamo, Kristin; Chung, Stephen W.
Abstract Background The aim of the present study was to determine the utility of computed tomography (CT) and magnetic resonance imaging (MRI) anatomic mapping in the detection of biliary and vascular anomalies prior to a living liver donor (LLD) operation. Methods A retrospective study of all LLD patient charts, operative and radiology reports from 1 January 2002 to 1 January 2012 was conducted. Primary post‐operative outcomes assessed included mortality, re‐operation, readmission and need for endoscopic or percutaneous intervention. Sensitivity and specificity of MR and CT pre‐operative screening was calculated against the gold standard of intra‐operative findings. Results A total of 34 donors had an average age of 38 years (range: 22–58) with a body mass index (BMI) of 25.6 kg/m2 (range: 19.8–32.5) and a length of stay (LOS) of 10.1 days (range: 5–41). There were no donor mortalities. Sensitivity and specificity of CT was 70.0% and 91.3%, and of MRI screening 23.1% and 100.0%, respectively. Patients with inaccurate pre‐operative CT or MRI did not have an increased risk of complications. Conclusions Even although it was specific, pre‐operative MR screening missed up to 77.0% of biliary anomalies. An impeccable surgical technique remains the key in preventing biliary complications of a living donor hepatectomy where pre‐operative MRI screening is false.